Psychological Counceling Center for Students – Need, Desire, Necessity - Ranđelović, Dušan J.; Mitrović, Milica Z.; Todorović, Dušan Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The period of studying is a time of actualization of the capacities of the individual in almost every aspect of life. The students face changes related to the stage of development they are going through, and to which new requests of adaptation are added during professional qualification. The increased rate of psychological problems shows a necessity for existence of student services that provide psychological help. The research results point out the positive effect of counseling and the importance of university counseling services for the students, the effect on their academic success, subjective welfare and their remaining at the faculty. The pilot-project „Psychological Counseling Center for Students” at the University of Nis is one of the largest and most permanent projects of this kind among universities of the region. The services of the counseling are completely free, and they are realized through three sectors: Counseling, Education and the Research Sector. Work reports of The Counseling service show that there is a need for this kind of psychological services and that the students are interested in attending seminars and debates where different aspects of mental health would be considered. The institutionalization of the above mentioned project, with the possible expansion of the network of psychological counseling services of this type in the region would give greater effects and contribute to the more comprehensive work concerning protection and improvement of the mental health of the students not only in Serbia, but also in surrounding countries.
Keywords: prevention; psychological counseling center; students